Pengembangan Daya Tarik Wisata Alam Kebun Raya Bogor - Rizki Nugraha; Venda Irlani (Jurnal Ilmiah Wahana Pendidikan, 2023)
Strengthened by the Law of the Republic of Indonesia No. 10 of 2009, tourist attraction is explained as everything that has uniqueness, convenience and value in the form of a diversity of natural, man-made and man-made assets that are targeted or visited by tourists. the development of this tourist attraction is very important in tourism resources in the Bogor Botanical Gardens. The purpose of this research is to increase the development of the existing tourism sector in Indonesia through government attraction and community participation in the development of Indonesian tourism. This journal was prepared using qualitative methods. From this research discusses the development of tourist attraction by tourism Bogor Botanical Gardens located on Jl. Ir. H. Juanda No.13, Paledang, Central Bogor District, Bogor City, West Java 16122